IMPROVING STUDENT’S VOCABULARY ACHIEVEMENT IN WITING DESCRIPTIVE TEXT THROUGH MAKE A MATCH METHOD - Irma Lely Lumban Gaol; Johan Sinulingga (Universitas Negeri Medan, 2013)
This study is concerned with the improving student’s vocabulary achievement in writing descriptive text through Make a Match Method. The objective of this study was to discover whether the use of Make a Match Method could significantly improve students’ vocabulary achievement in writing descriptive text. This study was conducted by applying Classroom Action Research which was carried out in two cycles in six meetings. The subject of this study was students of SMA Negeri 1 Pollung which consisted of 34 students. The instruments for collecting data were descriptive writing test, observation sheet, questionnaire sheet, and diary notes. The techniques for data analysis were quantitative and qualitative. It was found that teaching-learning process ran well. Students were active, enthusiastic and interested on writing descriptive text. The result of this study showed that the use of Make a Match Method significantly improved student’s vocabulary achievement in writing descriptive text.